Assessing the quality of life in informal settlements in Miandoab - farhad judi; rahim sarvar; sedigheh hassani mehr (تحقیقات کاربردی علوم جغرافیایی)
Recognizing and measuring the quality of life in urban areas that are the result of the actions of urban management and other public and private institutions is a very vital issue. Due to the lack of quality of urban life in informal urban settlements, it is possible to provide a roadmap for urban management and awareness of responsible institutions of the current situation and action to achieve the desired situation. The purpose of this study is to assess the quality of life in informal settlements in Miandoab. The research method is descriptive-analytical and based on data collection in the field through a questionnaire. The validity of the instrument and its reliability were confirmed by Cronbach's alpha greater than 0.70. The statistical population of the study consists of 11545 citizens living in informal settlements in Miandoab. The sample size was determined based on Cochran's formula, 313 people. The test results show that four indicators of social, economic, physical and environmental quality of life in informal settlements of Miandoab were significant at a level of less than 0.05. Examination of the direction of significance indicates the inappropriateness of the indicators. The ANOVA test also confirmed that the 10 neighborhoods studied in terms of social, physical and environmental indicators are significantly different at the level of less than 0.05, but in the field of economic indicators (significance level equal to 0.094) there are the same conditions. Assessing the effect of urban management on improving the quality of life through structural equations also confirmed that the rate of explanation for the social index is equal to 0.97; For economic index equal to 0.48; It is equal to 0.93 for the physical index and 0.55 for the environmental index. Therefore, the greatest effect of urban management is on the social index and then the physical.